Control of surfaces in confined spaces : Tab-aileron control system development - Rupert, Francois Johannes (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.